Clinical Pharmacy Congress 2022. Issue 1 (9th February 2023) - Unknown
Abstract : The Clinical Pharmacy Congress 2022 marked its 11th birthday, celebrating the return to normality after the pandemic with the delivery of over 250 educational sessions by industry experts over two days, to enhance the professional and personal development of attendees. Joy Ogden covers some highlights of the conference on thought‐provoking subjects such as risks of dementia with antimuscarinics and sessions on clinical priorities in epilepsy and headache.